2022
DOI: 10.1186/s12890-022-01905-3
|View full text |Cite
|
Sign up to set email alerts
|

The zinc transporter ZIP12 regulates monocrotaline-induced proliferation and migration of pulmonary arterial smooth muscle cells via the AKT/ERK signaling pathways

Abstract: Background The zinc transporter ZIP12 is a membrane-spanning protein that transports zinc ions into the cytoplasm from the extracellular space. Recent studies demonstrated that upregulation of ZIP12 is involved in elevation of cytosolic free zinc and excessive proliferation of pulmonary arterial smooth muscle cells (PASMCs) induced by hypoxia. However, the expression of ZIP12 and its role in pulmonary arterial hypertension (PAH) induced by monocrotaline (MCT) in rats have not been evaluated pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 75 publications
(77 reference statements)
2
6
0
Order By: Relevance
“…Inhibition of ZIP12 expression significantly or partially prevented hypoxia-induced PAH, RV hypertrophy and vascular remodeling than wild type rats, suggesting the essential role of ZIP12 expression in the pathogenesis of PH. This important finding was further supported by the subsequent studies with different conditions 157 , 158 .…”
Section: Metals and Phsupporting
confidence: 71%
“…Inhibition of ZIP12 expression significantly or partially prevented hypoxia-induced PAH, RV hypertrophy and vascular remodeling than wild type rats, suggesting the essential role of ZIP12 expression in the pathogenesis of PH. This important finding was further supported by the subsequent studies with different conditions 157 , 158 .…”
Section: Metals and Phsupporting
confidence: 71%
“…Members of the solute carrier 39 gene family encoding zinc transport proteins contribute to critical mechanisms, by which zinc homeostasis can be maintained across a wide range of species. Their main function is to promote the uptake of the extracellular environment and transport Zn 2+ into cells [ 40 ]. A previous study showed that oxidative stress reduced the expression of zinc transporters in hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary vascular remodeling mainly occurs in pulmonary artery smooth muscle cells (PASMCs), endothelial cells and fibroblasts in the vascular wall. Excessive PASMCs proliferation and migration tends to cause pulmonary vascular remodeling and trigger PH [ 30 ]. In this study, we found that SOCS5 expression was low in PASMCs, and overexpression of SOCS5 inhibited the abnormal proliferation and migration of HPASMCs under hypoxia in vitro, while knockdown of SOCS5 promoted it.…”
Section: Discussionmentioning
confidence: 99%